CD4+ T Cells Specific for C. difficile Toxins are a Marker of Patients with Active Relapsing Disease. (4th October 2017) - Cook, Laura; Wong, May; Rees, William; Lau, Torey; Levings, Megan; Steiner, Theodore
Abstract: Background: The bacterial pathogen Clostridium difficile is the leading cause of nosocomial infectious diarrhea. Although C. difficile infection (CDI) can be treated with antibiotics, approximately 25% of patients relapse after treatment. The pathogenicity of CDI requires the activities of its toxins, TcdA and TcdB, but T cell-mediated responses to these toxins remain uncharacterized. Methods: We enrolled two cohorts of patients, one with newly acquired CDI ( n = 14) and the other with relapsing CDI ( n = 25); and healthy volunteers with no history of CDI ( n = 12). We measured peripheral blood CD4 + T cell responses to the toxins using a whole blood flow cytometry assay that identifies antigen-specific CD4 + T cells by co-expression of CD25 and OX40 following 44h incubation with antigen (Fig 1 ). Results: We found that in patients with recurring CDI, T cell responses to TcdB were significantly higher than in healthy controls (median 1.04% vs. 0.18%; P = 0.003, Fig 2 ). In contrast, TcdA T cell responses and anti-TcdA/TcdB IgG titres were not different between recurring patients and controls. TcdB, but not TcdA, T cell responses were significantly higher in recurring CDI compared with newly acquired CDI (median 1.04% vs. 0.44%; P = 0.032). In both patient cohorts TcdB-specific CD4+ T cells were functionally heterogeneous, on average: 25% expressed the gut homing marker integrin β7; there was a 1:1 ratio of Tregs to T effectors; and T effectors contained Th1, Th2 and Th17 cells at a 1.5:1:3 ratio. The proportion of Th1 and Th17 cells within TcdB-specific CD4+ T cells was also significantly reduced in recurring, compared with newly acquired, CDI (Fig 3) . Analysis of sorted TcdB-specific CD25+OX40+ cells confirmed specificity for TcdB and polarization towards Th17 cells, which are important for intestinal anti-pathogen immunity. Conclusion: This is the first investigation of T cell immunity to C. difficile toxins. Our data show that anti-TcdB CD4 + T cell responses are a more specific marker of disease than IgG titres. Tracking how toxin-specific CD4 + T cell responses change following treatment and/or vaccination not only has the potential to predict relapse, but also to deliver insight into how CD4 + T cell memory develops in response to this prevalent pathogen. Disclosures: All authors: No reported disclosures.